TEKNIK PEMBUATAN TATO TRADISIONAL JEPANG IREZUMI SERTA PERKEMBANGANNYA - Mulyadi, Budi (Vocational College of Diponegoro University, 2017)
This research entitled The Technique of Making Japanese TraditionalTatto (irezumi) and It’s Developing The main goal of this reserach is to know about various of the technique of making Japanese traditional tatto ( irezumi ) and developing of Japanese traditional tatto. This research uses field reserach. Main method are observation, and interpretation. The research show irezumi has many technicuein making proses it such as tebori, tsukibori, hanebori etc. Also irezumi has been developed in making proces so that change the funcution of irezumi it self.